Ambipolar electrostatic field in dusty plasma. (23rd April 2022) - Hadid, L.Z.; Shebanits, O.; Wahlund, J.-E.; Morooka, M.W.; Nagy, A.F.; Farrell, W.M.; Holmberg, M.K.G.; Modolo, R.; Persoon, A.M.; Tseng, W.L.; Ye, S.-Y.
Abstract : We study the effect of negatively charged dust on the magnetic-field-aligned polarisation electrostatic field (E_ ) using Cassini's RPWS/LP in situ measurements during the 'ring-grazing' orbits. We derive a general expression for E_ and estimate for the first time in situ E_ Vert (approximately 10^-5 V m^-1 ) near the Janus and Epimetheus rings. We further demonstrate that the presence of the negatively charged dust close to the ring plane (Z 0.11 R_s ) amplifies E_ Vert by at least one order of magnitude and reverses its direction due to the effect of the charged dust gravitational and inertial forces. Such reversal confines the electrons at the magnetic equator within the dusty region, around 0.047 R_s above the ring plane. Furthermore, we discuss the role of the collision terms, in particular the ion–dust drag force, in amplifying E_ . These results imply that the charged dust, as small as nanometres in size, can have a significant influence on the plasma transport, in particular ambipolar diffusion along the magnetic field lines, and so their presence must be taken into account when studying such dynamical processes.